Analyses and Evaluation of Wireless Local Area Network in Vehicular Mobility Scenarios - Jansons, J.; Petersons, E.; Bogdanovs, N. (Elektronika ir Elektrotechnika, 2013)
Vehicle-to-infrastructure (V2I) communication based on wireless local area network (WLAN) technology can provide users in-motion to obtain Internet connectivity. In this paper we present an experimental study of IEEE802.11n with diminished settings compared to the legacy system using off-the-shelf devices in V2I small scale scenario. In order to evaluate the V2I the type of communication in the large scale scenario, in this paper we propose an analytic model to characterize the goodput of WLAN-based networks using Markov process. DOI: http://dx.doi.org/10.5755/j01.eee.19.2.3477